2D-materials-integrated optoelectromechanics: recent progress and future perspectives. (1st February 2023) - Peng, Mingzeng; Cheng, Jiadong; Zheng, Xinhe; Ma, Jingwen; Feng, Ziyao; Sun, Xiankai
Abstract: The discovery of two-dimensional (2D) materials has gained worldwide attention owing to their extraordinary optical, electrical, and mechanical properties. Due to their atomic layer thicknesses, the emerging 2D materials have great advantages of enhanced interaction strength, broad operating bandwidth, and ultralow power consumption for optoelectromechanical coupling. The van der Waals (vdW) epitaxy or multidimensional integration of 2D material family provides a promising platform for on-chip advanced nano-optoelectromechanical systems (NOEMS). Here, we provide a comprehensive review on the nanomechanical properties of 2D materials and the recent advances of 2D-materials-integrated nano-electromechanical systems and nano-optomechanical systems. By utilizing active nanophotonics and optoelectronics as the interface, 2D active NOEMS and their coupling effects are particularly highlighted at the 2D atomic scale. Finally, we share our viewpoints on the future perspectives and key challenges of scalable 2D-materials-integrated active NOEMS for on-chip miniaturized, lightweight, and multifunctional integration applications.